Features of the influence of the antioxidant ethylmethylhydroxypyridine malate and the drug ubidecarenone on plasma concentrations of ubiquinone, ubiquinol and the redox state of coenzyme Q10 - V. I. Zozina; S. N. Kondratenko; E. V. Shikh; L. M. Krasnykh; E. S. Melnikov; V. G. Kukes (LLC "Publisher OKI", 2024)
Relevance. Coenzyme Q10 is one of the main components that maintain the balance of the body's redox regulatory system. Although some studies have examined plasma concentrations of CoQ10 in various diseases, the distribution of ubiquinol and ubiquinone, as well as the redox state of CoQ10, remain largely unexplored. The purpose of the study. The purpose of the study was to study the ratio of ubiquinone and ubiquinol concentrations in patients with chronic heart failure (CHF) administrating the antioxidant ethylmethylhydroxypyridine malate and the domestic drug ubidecarenone (CoQ10 drug). Methods. The study included 58 patients with functional class (FC) of CHF 0−III (according to NYHA), who were divided into 2 groups for subsequent assessment of the effect of ethylmethylhydroxypyridine malate and ubidecarenone on endogenous plasma concentrations of total CoQ10, ubiquinol and ubiquinone. The concentrations of the studied substances were determined by HPLC-MS/MS in the multiple reaction monitoring mode. Results. The study revealed that with additional administration of the drug ubidecarenone, there was an increase in the concentration of coenzyme Q10 (+25.0 Δ%), a significant increase in the concentration of ubiquinol (+43.4 Δ%), as well as a sharp increase in redox state (+74.6 Δ%) compared to the control group. During administration of ethylmethylhydroxypyridine malate in addition to standard therapy, patients experienced a statistically significant increase in the concentration of coenzyme Q10 (+20.22 Δ%), a significant increase in the concentration of ubiquinol (+25.0 Δ%) and ubiquinone (+17.7 Δ%) according to compared with a control group receiving standard therapy. Conclusion. With the additional administration of ethylmethylhydroxypyridine malate and ubidecarenone to standard therapy, a statistically significant increase in the concentration of total CoQ10 is observed. However, when administrating ubidecarenone, a sharp increase in the redox state of CoQ10 is observed due to its reduced form - ubiquinol. While during administration of ethylmethylhydroxypyridine malate, it is observed an unreliable but positive trend towards an increase in the redox state of CoQ10 due to a statistically significant increase in the concentration of both ubiquinone and ubiquinol.